2018
DOI: 10.3389/fmicb.2018.01798
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Gut Microbiota Establishment and Metabolome Characteristics Between Low- and Normal-Birth-Weight Piglets During Early-Life

Abstract: Low-birth-weight (LBW) piglets are at a high-risk for postnatal growth failure, mortality, and metabolic disorders later in life. Early-life microbial exposure is a potentially effective intervention strategy for modulating the health and metabolism of the host. Yet, it has not been well elucidated whether the gut microbiota development in LBW piglets is different from their normal littermates and its possible association with metabolite profiles. In the current study, 16S rRNA gene sequencing and metabolomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
82
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 87 publications
21
82
4
Order By: Relevance
“…In the present study, Firmicutes and Bacteroidetes were the most dominant phyla in both colonic and caecal mucosa of NBW and LBW pigs, which was consistent with the previous studies in pigs (61). At the genus level, Streptococcus was predominant in the colonic mucosal microbiota in our study, which was also discovered in the fecal sample of LBW piglets (60). The genus Lactobacillus was predominant in the caecal mucosal microbiota, which was in accordance with a previous study (62).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, Firmicutes and Bacteroidetes were the most dominant phyla in both colonic and caecal mucosa of NBW and LBW pigs, which was consistent with the previous studies in pigs (61). At the genus level, Streptococcus was predominant in the colonic mucosal microbiota in our study, which was also discovered in the fecal sample of LBW piglets (60). The genus Lactobacillus was predominant in the caecal mucosal microbiota, which was in accordance with a previous study (62).…”
Section: Discussionsupporting
confidence: 93%
“…Intestinal symbiotic microbes could regulate the intestinal epithelial barrier function by their nature of resistance to pathogens (59). Our findings showed that the microbial diversity (a-and b-diversity) of the colonic and caecal mucosa did not change between NBW and LBW pigs, which was consistent with the previous results for analysis of their fecal microbiota during the neonatal stage (60). In the present study, Firmicutes and Bacteroidetes were the most dominant phyla in both colonic and caecal mucosa of NBW and LBW pigs, which was consistent with the previous studies in pigs (61).…”
Section: Discussionsupporting
confidence: 91%
“…46 Only a very recent report described the microbiota composition in six regions of the gastro-intestinal tract at eight post-natal time-points. Indeed, if we consider fecal samples as a proxy of colonic samples, Li et al observed an increase in fecal richness and diversity with age (PND3 to 21) and a gradual evolution of the fecal microbiota composition from PND3 to 21 45 as observed in the colon in our study. Indeed, if we consider fecal samples as a proxy of colonic samples, Li et al observed an increase in fecal richness and diversity with age (PND3 to 21) and a gradual evolution of the fecal microbiota composition from PND3 to 21 45 as observed in the colon in our study.…”
Section: Discussionsupporting
confidence: 62%
“…3 The temporal and regional variations that we reported are in line with these published data. Fecal microbiota at PND21 was populated by Lactobacillus (Lactobacillacea), Ruminococcus (Ruminococcaceae), Prevotella (Prevotellaceae), and Rikenella (Rikenellaceae) 45 as observed in the colon at PND28 in our study. Fusobacterium (Fusobacteriaceae) and Bacteroides (Bacteroidaceae) were predominant in the feces at PND3 but decreased at older stages.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation